The Effect Of Shopping Emotion And Perceived Risk On Purchasing Decisions Through Impulsive Buying As An Intervening Variable In Shopee E-Commerce Consumers - Marhadi Marhadi; Gustina Adinda Putri; Aida Nursanti; Cifebrima Suyastri (Institute of Computer Science (IOCS), 2022)
The research was conducted with the aim of knowing the effect of shopping emotion and perceived risk on purchasing decisions through impulsive buying on E-Commerce Shopee consumers in Pekanbaru City. Questionnaires were distributed to 126 respondents using the Purposive Sampling technique and processed using the Structural Equation Modeling – Partial Least Square analysis method with SmartPLS software version 3.2.9.The results showed that there was a positive and significant influence between shopping emotion on purchasing decisions. There is a positive and significant effect between shopping emotion on impulsive buying. There is a positive and significant influence between perceived risk on purchasing decisions. There is a positive and significant effect between perceived risk on impulsive buying. There is a positive and significant influence between impulsive buying on purchasing decisions.